Both Light-Induced SA Accumulation and ETI Mediators Contribute to the Cell Death Regulated by BAK1 and BKK1 - Gao, Yang; Wu, Yujun; Du, Junbo; Zhan, Yanyan; Sun, Doudou; Zhao, Jianxin; Zhang, Shasha; Li, Jia; He, Kai (Frontiers in Plant Science, 2017)
Receptor-like kinases BAK1 and BKK1 modulate multiple cellular processes including brassinosteroid signaling and PRR-mediated PTI in Arabidopsis. Our previous reports also demonstrated that bak1 bkk1 double mutants exhibit a spontaneous cell death phenotype under normal growth condition. With an unknown mechanism, the cell death in bak1 bkk1 is significantly suppressed when grown in dark but can be quickly induced by light. Furthermore, little is known about intrinsic components involved in BAK1 and BKK1-regulated cell death pathway. In this study, we analyzed how light functions as an initiator of cell death and identified ETI components to act as mediators of cell death signaling in bak1 bkk1. Cell death suppressed in bak1 bkk1 by growing in dark condition recurred upon exogenously treated SA. SA biosynthesis-related genes SID2 and EDS5, which encode chloroplast-localized proteins, were highly expressed in bak1-4 bkk1-1. When crossed to bak1-3 bkk1-1, sid2 or eds5 was capable of efficiently suppressing the cell death. It suggested that overly produced SA is crucial for inducing cell death in bak1 bkk1 grown in light. Notably, bak1-3 or bkk1-1 single mutant was shown to be more susceptible but bak1-3 bkk1-1 double mutant exhibited enhanced resistance to bacterial pathogen, suggesting immune signaling other than PTI is activated in bak1 bkk1. Moreover, genetic analyses showed that mutation in EDS1 or PAD4, key ETI mediator, significantly suppressed the cell death in bak1-3 bkk1-1. In this study, we revealed that light-triggered SA accumulation plays major role in inducing the cell death in bak1 bkk1, mediated by ETI components.